Description of Types of Wounds on Living Victims Due to Persecution who Come to the Emergency Installation of Drs. H. Amri Tambunan Hospital, Deli Serdang, in 2020-2021 - Abdul Gafar Parinduri; Muhammad Reza Restu Fauzi (Buletin Farmatera, 2022)
Background. About 50-70% of cases that come to the Emergency Installation are cases of injury or trauma. Injuries to these patients can occur as a result of accidents, abuse, attempted suicide, disasters, and terrorist attacks. Aim: This study aims to describe the types of injuries to living victims due to abuse who came to the Emergency Installation of drs. H. Amri Tambunan Hospital, Deli Serdang from January 1, 2021 to December 31, 2021. Method: The research design is an observational study using analytical descriptive methods and a retrospective approach using the data from visum et repertum report of survivors as a result of persecution who came to the Emergency Installation of drs. H. Amri Tambunan Hospital, Deli Serdang. Results: Out of 273 survivors of abuse, 69.6% involved mechanical trauma and the majority of mechanical trauma occurred to females (52.6%) and the most common pattern of injury was abrasions (58.2%). Conclusion: Based on the results of this study, the most common type of wound encountered was mechanical trauma with a pattern of abrasions.